Oath of Government Employees-Based Standards and Organizational Commitment in a Local Government Unit in Central Luzon, Philippines - Soriano, Imelda (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2021)
The study aimed to assess the organizational commitment and the internalization of the standards contained in the Oath of Government Employees (Panunumpa ng Kawani ng Gobyerno) based on the experience of the employee of the Local Government Unit of Olongapo. It will specifically focus on four key result areas reflected in the pledge of commitment: honesty and integrity, proper use of government property, fight against corruptions, technical and professional competencies. The researcher used a descriptive research method and utilized a cross-sectional design with the questionnaire as the main data gathering tool. The population of the study consisted of the employees in the different service-delivery units of a highly urbanized city in Central Luzon, Philippines. A sample size representing ten percent (10%) of the total population determined the respondents for the study. The sample respondents were selected among the different service-delivery units of the local government unit using a simple random sampling technique. This study intended to prove the significant difference in the organizational commitment of employees in the local government unit in terms of gender, age, and length of service. Furthermore, the research also tried to determine the relationship between the Oath of Government Employees – Based Standards and Employees Organizational Commitment in the local government unit of the involved highly urbanized city. The result of the study will serve as a basis to develop a proposed Service Charter for each of the service-delivery units of the local government of the City.